Synthesis of Polymer-Drug Conjugates Using Natural Polymer: What, Why and How? - Sagita, Erny; Syahdi, Rezi Riadhi; Arrahman, Arif (Pharmaceutical Sciences and Research, 2018)
For years, natural polymers have played a significant role in pharmaceutical field due to their biocompatibility and biodegradability. In Indonesia, most research in natural polymers focus on application of the polymers as inert pharmaceutical excipients or as drug matrix in micro- and nano- particle. Meanwhile, research about polymers in the world (mostly synthetic polymers) have been progressed to advanced drug delivery system. In this system, the polymer can act as either pharmacologically active molecules, or sophisticated carrier in targeted prodrug delivery system. The latter is called polymer-drug conjugates, a system where the drugs are covalently attached to a polymeric carrier, rather than simply entrapped in polymer matrix. Natural polymers have been one of the materials to use for the carrier due to their biocompatibility and biodegradability. This review article emphasizes the opportunity, challenges and strategies to use natural polymers as carrier in polymer-drug conjugates. Moreover, we also discuss some aspects in regards of the synthesis and analysis, to give some perspectives and encouragement for the Indonesian researcher who are interested in exploring this research field.